2018
DOI: 10.1111/cpr.12563
|View full text |Cite
|
Sign up to set email alerts
|

Role of pyroptosis in cardiovascular disease

Abstract: Cardiac function is determined by the dynamic equilibrium of various cell types and the extracellular matrix that composes the heart. Cardiovascular diseases (CVDs), especially atherosclerosis and myocardial infarction, are often accompanied by cell death and acute/chronic inflammatory reactions. Caspase-dependent pyroptosis is characterized by the activation of pathways leading to the activation of NOD-like receptors, especially the NLRP3 inflammasome and its downstream effector inflammatory factors interleuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
229
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(234 citation statements)
references
References 141 publications
4
229
1
Order By: Relevance
“…It should be noted that the pathological mechanisms of endothelial dysfunction are complicated and need to be further elucidated. Diverse risk factors, including genetics, aging, and obesity, are reported to be involved in cardiovascular disease [30]. Animal experimentation is an important method for exploring the pathogenesis and treatment of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the pathological mechanisms of endothelial dysfunction are complicated and need to be further elucidated. Diverse risk factors, including genetics, aging, and obesity, are reported to be involved in cardiovascular disease [30]. Animal experimentation is an important method for exploring the pathogenesis and treatment of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As ABCA1 can regulate cholesterol metabolism and inflammation, indicating MEG3 could indirectly affect cholesterol metabolism and inflammation. It was shown that MEG3 enhanced pyroptosis, a highly inflammatory form of programmed cell death, in ox-LDL treated HCAECs by sponging miR-223 targeting NOD-like receptor protein 3 (NLRP3) (85,114). Consistently, MEG3 was upregulated in ox-LDL treated RAW264.7 cells and increased secretion of TNF-α and IL1β by sponging miR-204, which targeted the cyclin-dependent kinase inhibitor 2A (CDKN2A) (86).…”
Section: Meg3mentioning
confidence: 92%
“…Pyroptosis, a novel pro‐inflammatory programmed cell death process, participates in pathogenesis of CVD . MALAT1 promotes high glucose or ox‐LDL‐induced pyroptosis of ECs partly by affecting the expression of pyrin domain 3 (NRLP3) through competitively binding miR‐22 .…”
Section: Malat1 and Pathophysiology Of Cvdsmentioning
confidence: 99%
“…36 Conversely, some studies indicated that angiogenesis was also associated with the growth of atherosclerotic lesions and plaque destabilization. 37 Many studies showed that MALAT1 was largely induced in ECs and involved in the pathology of vascular diseases [29][30][31][32] (Table 1).…”
Section: Malat1 and Vascular Diseasesmentioning
confidence: 99%